PROFIL AKNE VULGARIS DI RSUP Prof. Dr. R. D. KANDOU MANADO PERIODE 2009-2011 - Mizwar, Muhammad; Kapantow, Marlyn Grace; Suling, Pieter Levinus (e-CliniC, 2013)
Abstract: Acne vulgaris is a chronic inflammatory disease of pilosebaceous follicles that commonly occurs in adolescence and can heal itself. The purpose of this study was to determine the profile of acne vulgaris in Dermatovenereology of Prof. Dr. R. D. Kandou Manado in 2009-2011. This study was conducted retrospectively in patients with acne vulgaris who came to the Dermatology clinic in 2009-2011. The data were recorded from  medical records of the amounts of patients, gender, age, occupation / education, lesion location, and the type of acne. The results showed that of a total of 10003 visits in 2009-2011 there of 121 patients (3.59%) were new cases of acne vulgaris, acne vulgaris in patients dominance of female patients by 75 patients (61.9%), the age group most at 15-24 years old is 76 patients (62.8%), the highest educational status on the student group is 73 patients (60.3%), the most lesions location are on the face, most types of acne is papulopustular. Key words: acne vulgaris, inflammation, pilosebaceous    Abstrak: Akne vulgaris adalah penyakit peradangan menahun folikel pilosebasea yang umumnya terjadi pada masa remaja dan dapat sembuh sendiri. Tujuan dari penelitian ini untuk mengetahui profil akne vulgaris di poliklinik Kulit dan Kelamin RSUP Prof Dr R. D. Kandou Manado pada tahun 2009–2011. Penelitian ini dilakukan secara retrospektif pada pasien dengan akne vulgaris yang datang ke poliklinik  Kulit dan Kelamin pada tahun 2009–2011. Dilakukan pencatatan data dari catatan medik mengenai jumlah pasien, jenis kelamin, usia, pekerjaan/pendidikan, lokasi lesi, dan jenis akne. Hasil yang diperoleh menunjukkan bahwadari total 10003 kunjungan pada tahun 2009–2011 terdapat 121pasien (3,59%) merupakan penderita baru akne vulgaris, pasien akne vulgaris di dominasi pasien perempuan sebanyak 75 pasien (61,9%), kelompok usia terbanyak pada usia 15 – 24 tahun yaitu 76 pasien (62,8%), status pendidikan terbanyak  pada kelompok pelajar yaitu 73 pasien (60,3%), lokasi lesi terbanyak yaitu di bagian wajah, jenis akne terbanyak yaitu papulopustuler. Kata kunci: akne vulgaris, pilosebasea, radang